Citrulline malate supplementation might potentiate post-exercise hypotension in hypertensives: A 24-hour analysis - Casonatto, J.; Cavalari, J. V.; Goessler, K. F.; Christofaro, D. G.D. [UNESP]; Polito, M. D.; Enokida, D. M.; Grandolfi, K. (Elsevier, 2019)
Objective: The present study was designed to investigate whether citrulline malate supplementation might influence the acute post-exercise blood pressure response in hypertensives. Methods: Forty adults, hypertensive and sedentary, were randomly assigned to one of four experimental groups (control-placebo, control-citrulline, exercise-placebo, and exercise-citrulline). The volunteers ingested a sachet with placebo (6 grams) or citrulline malate (6 grams). During the exercise session, individuals performed 40 min of walking/running on a treadmill at 60–70% of reserve heart rate. For the control's session, they remained seated at rest for 40 min. Office blood pressure was taken every 10 min until completing 60 min after the experimental session. The ambulatory blood pressure device was programmed to take the readings every 20 min (awake time) and every 30 min (sleep time) over the course of 24 h of monitoring. Furthermore, heart rate variability was measured. Results: Considering systolic blood pressure, the aerobic exercise combined with citrulline malate supplementation promoted an additional blood pressure reduction when compared to isolated exercise during 60 min after the experimental session (−15.01 ± 2.57 mmHg vs. −6.30 ± 3.60 mmHg, P = 0.03). Additionally, considering diastolic blood pressure, exercise combined with citrulline malate showed a significant effect for the “awake” period (−13.93 ± 1.96 mmHg vs. −6.85 ± 2.57 mmHg, P = 0.027) and over the course of 24 h (−13.83 ± 1.93 mmHg vs. −7.64 ± 2.58 mmHg, P = 0.047). Conclusion: Acute citrulline malate supplementation might potentiate the post-exercise hypotension effects in hypertensive individuals.
La supplémentation en malate de citrulline pourrait potentialiser l'hypotension post-exercice chez les hypertendus
Keywords: Ambulatory blood pressure monitoring; Blood pressure; Citrulline malate; Dietary supplements; Exercise; Hypertension